KARAKTERISASI MORFOLOGI SENGON (Paraserianthes falcataria L. Nielsen) HASIL MUTASI RADIASI SINAR GAMMA Morphological Characterization of Sengon (Paraserianthes falcataria L. Nielsen) Gamma Radiation Mutation Results - Roisatuz Zakiyah; Ulfah Juniarti Siregar; N. Sri Hartati (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2017)
Mutation is a process of change in genetic structure of particular organisme. Genetic changes due to mutation can produce new characteristic and increase genetic diversity, which will be utilized for improvement program. Several artificial mutation programs have proved to produce new superior individual. One common artificial mutation used is gamma radiation. This study aimed to characterize 9 years old gamma irradiated sengon trees, with doses 0, 5, 10, and 15 krad based on its morphological characters, wood density, resistant to diseases. The observed parameters were tree diameter, height, volume, clear bole height, stem straightness, permanent branch, number of branches, canopy length, wood density and resistance to gall rust disease. Average values of all parameters of mutant lines does not differ significantly from control trees, however some individuals have better morphological characters than others. Mutant lines with 5 krad dose have close association with permanent branch and stem straightness, 15 krad dose with volume, diameter, height and crown length, while 10 krad with number of branches. Average wood density of mutant lines did not differ significantly from control either, with highest value belonged to 10 krad dose. Selected superior tree candidates were individuals with number 5.07, K1, 15.27, and 15 NN.Key word: breeding, characterization, mutation, sengon.